Femtosecond ytterbium-doped fiber laser mode-locked by carboxyl-functionalized graphene oxide saturable absorber. (30th November 2017) - Hou, Lei; Lin, Qimeng; Wang, Yonggang; Chen, Zhendong; Sun, Jiang; Guo, Hongyu; Bai, Yang; Chen, Haowei; Lu, Baole; Bai, Jintao
Abstract: In contrast with graphene oxide (GO), carboxyl-functionalized graphene oxide (GO-COOH) is more appropriate for fabricating saturable absorbers (SAs) with high modulation depth and low nonsaturable loss because of its higher solubility in water. Here, we present a femtosecond mode-locked ytterbium-doped fiber (YDF) laser based on GO-COOH SA and a nonlinear polarization rotation effect. A mode-locked laser with a center wavelength of 1027 nm, an average output power of 53.5 mW (44.3% conversion efficiency), a fundamental repetition rate of 22 MHz, a pulse duration of 239 fs, and a signal-to-noise ratio of up to 75 dB is obtained.